Mesoporous Bioactive Glass Combined with Graphene Oxide Quantum Dot as a New Material for a New Treatment Option for Dentin Hypersensitivity - Sung-Ae Son (Nanomaterials, 2020)
Dentin hypersensitivity is one of the most common clinical conditions usually associated with exposed dentinal tubules. The purpose of this study was to identify the potential of a graphene oxide quantum dot coating for mesoporous bioactive glass nanoparticles as a new material for the treatment of dentin hypersensitivity by investigating its mineralization activity and dentinal tubules sealing. Mesoporous bioactive glass nanoparticle was fabricated by modified sol-gel synthesis. X-ray diffraction was performed to characterize the synthesized nanoparticle Fourier transform infra-red spectroscopy investigated the functionalized surfaces. The distribution of the specific surface area and the pore size was measure by Pore size analysis. The morphology of sample was observed by Field Emission Scanning Electron Microscope (FESEM) and Field Emission Transmission Electron Microscope (FETEM). After disk-shaped specimens of mesoporous bioactive glass nanoparticles and graphene oxide quantum dot coated mesoporous bioactive glass nanoparticles (n = 3) were soaked in the simulated body fluid for 0, 1, 5, 10,and 30 days, the amount of ions released was observed to confirm the ionic elution for mineralization. Sensitive tooth model discs (n = 20) were applied with two samples and evaluated the dentinal tubule sealing ability. The spherical mesoporous bioactive glass nanoparticles and graphene oxide quantum dot coated mesoporous bioactive glass nanoparticles with a diameter of about 500 nm were identified through FESEM and FETEM. The ion release capacity of both samples appeared to be very similar. The amount of ion released and in vitro mineralization tests confirmed that graphene oxide quantum dot coating of mesoporous bioactive glass nanoparticles did not inhibit the release of calcium, silicon and phosphate ions, but rather that graphene oxide quantum dot promoted hydroxyapatite formation. In the FESEM image of the sensitive tooth disc surface, it was observed that graphene oxide quantum dot coated mesoporous bioactive glass nanoparticles sealed tightly the dentinal tubules. The graphene oxide quantum dot coating of mesoporous bioactive glass nanoparticles not only showed the excellent dentinal sealing ability but also rapidly promoted mineralization while minimizing the size increase by coating the mesoporous bioactive glass nanoparticles.